Evaluasi Kebijakan Relokasi Pedagang UMKM di Pasar Rau Kota Serang - Sari, Marlita Jovita; Taniyah, Intan; Anggraeni, Shella; Diana, Diana; Rohmah, Nadiah Miftahul; Damayanti, Reza (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study is to evaluate the policy of relocating MSME traders in Rau Market, Serang City, and to see how it affects the traders’ economic activities. This study is qualitative and uses a descriptive approach. Most of the informants collected were MSME traders, market managers, fee officers, and buyers, who were selected purposively through interviews, documentation, and observation. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and drawing conclusions. The results show that the relocation policy has helped organize and manage Rau Market to make it safer, cleaner, and more comfortable for the public. However, not all traders felt the economic impact. Some traders experienced a decline in the number of buyers and profits due to the less strategic new location, while other traders actually saw an increase in transactions because of the location.